Feasibility study of establishing e-learning in Sarmayeh Bank - neda mohseni (Institute of Management fekrenoandish, 2020)
The present study was conducted to evaluate the feasibility of establishing e-learning in Sarmayeh Bank. The research method was descriptive. The statistical population in this study were learners, teachers, officials and experts in the fields of data engineering and education. 16 teachers and 300 learners for measuring the cultural component, 12 officials and data experts for measuring the technical component, and 12 officials and education experts for measuring the educational component were selected by census method. Data collection tools were Cultural, Technical and Educational Susceptibility Assessment Questionnaire. Data were analyzed by means of one-sample t-test and chi-square test. The findings of this study showed that the possibility of establishing a virtual education system in Sarmayeh Bank is approved and useful in terms of cultural, technical and educational infrastructure (P <0.01); Therefore, it is possible to establish e-learning in Sarmayeh Bank, and for the development of e-learning in the bank, more specialized staff should be trained, employees should be interested, and hardware and software facilities should be upgraded.